PENERAPAN MODEL PBL TERHADAP PENGUASAAN KONSEP BERHITUNG PERKALIAN MENGGUNAKAN MEDIA MULTIPLICATION BOARD PADA SISWA KELAS III SD NEGERI 25 BANDA ACEH - Cut Dewi Wulan; Rahmat Fitra; Intan Kemala Sari (STKIP Subang, 2026)
This research was motivated by the low mastery of multiplication concepts among elementary school students, which is caused by conventional learning that focuses on memorization. Such learning does not actively involve students and does not optimally utilize concrete learning media, resulting in less meaningful understanding of multiplication concepts. Therefore, the use of learning media that can help students understand multiplication concepts more effectively is needed. This study aimed to determine the improvement of students’ mastery of multiplication concepts in Grade III of SD Negeri 25 Banda Aceh through the use of Multiplication Board media. This research employed a quantitative approach with a pre-experimental design using a one group pretest–posttest design. The research subjects consisted of 30 students of Grade IIIA at SD Negeri 25 Banda Aceh. The research instruments included pretest and posttest questions to measure students’ mastery of multiplication concepts, as well as observation sheets to assess teacher and student activities during the learning process. The data were analyzed using a normality test and hypothesis testing with a t-test. The observation results showed that teacher activity reached a percentage of 95.33% and student activity reached 94.84%, both of which were categorized as very good. The t-test results indicated that the t-value was 35.66, while the t-table value was 1.699, meaning that the t-value was higher than the t-table value. This indicates an improvement in students’ mastery of multiplication concepts after using the Multiplication Board media. Based on these findings, it can be concluded that the use of Multiplication Board media can improve the mastery of multiplication concepts among Grade III students at SD Negeri 25 Banda Aceh. This study suggests that teachers use concrete learning media and encourage students to be more active in the learning process to enhance their understanding of multiplication concepts.